Compreendendo a influência da titânia no processamento da alumina eletrofundida marrom e sua caracterização para aplicações abrasivas - Passos, Edmilson Ricelli dos (2014)
Motivated by increased consumption of abrasive grains and the need of the abrasive market to develop roughing, polishing and increasiling efficient cutting tools, this work aimed to understand the influence of titania in obtaining "blue fired" fused aluminum oxide. This is a material obtained from the brown fused aluminum oxide, which is subjected to a heat treatment and consequently gets higher physical properties than the conventional brown aluminum oxide sold. To ensure that the "blue fired" aluminum oxide acquires the physicochemical characteristics required by the market, it should have a blue color and a friability inferior than brown fused aluminum oxide. Given the strong market demand for this type of product, Elfusa Geral de Eletrofusão LTDA has been working on improving the technology for obtaining industrial scale "blue fired" aluminum oxide since 2009. In this context Elfusa proposed the Coordinator of Process Engineering and Development, Edmilson Ricelli dos Passos, a technological and systematic study on the production of "blue fired" aluminum oxide. Thus, this work discusses the process of electrofusion of bauxite to obtain the "blue fired" aluminum oxide, as well as a comparison of the mechanical properties of this material with conventional brown fused aluminum oxides. Both process variables as the influence of the chemical composition were analyzed during the study, using physical and chemical characterization techniques. It has been proved in this work that controlling for time, temperature and atmosphere variables is essential for the production of "blue fired" aluminum oxide. The blue coloration of the aluminum oxide is explained by electronic transition optical phenomena is the formation of aluminum titanate phase, as some explanations found in the technical literature state.